2017
DOI: 10.15761/vrr.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of meteorological effects on the incidence of tick-borne encephalitis in the Czech Republic over a thirty-year period

Abstract: The goal is to analyse the effect of climatic factors on the incidence of tick-borne encephalitis (TBE) in three adjacent, high-incidence regions of the Czech Republic (CZ) that differed considerably in the baseline incidence and in the timing of high incidence period. The basis for the analysis were the meteorological data from a 30-year database of daily air temperature and precipitation measurements and time-matched reports of TBE cases defined by the onset of symptoms.A semi-parametric Poisson regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Our previous study showed near-ground temperature in the site of tick monitoring is the strongest predictor of tick activity, and showed a high correlation with local meteorological observations in Central Bohemia (Daniel et al, 2015 ). Similar observations apply to monitoring sites in northern Bohemia, northern Moravia, southern Bohemia, and in the Bohemian-Moravian Highlands (Daniel et al, 2016 ; Brabec et al, 2017 ). Hence seasonal discrepancies between numbers of active I. ricinus nymphs and TBE cases appear to be independent of locality.…”
Section: Discussionsupporting
confidence: 57%
“…Our previous study showed near-ground temperature in the site of tick monitoring is the strongest predictor of tick activity, and showed a high correlation with local meteorological observations in Central Bohemia (Daniel et al, 2015 ). Similar observations apply to monitoring sites in northern Bohemia, northern Moravia, southern Bohemia, and in the Bohemian-Moravian Highlands (Daniel et al, 2016 ; Brabec et al, 2017 ). Hence seasonal discrepancies between numbers of active I. ricinus nymphs and TBE cases appear to be independent of locality.…”
Section: Discussionsupporting
confidence: 57%
“…The increasing incidence of TBE was also observed in Poland [31], Norway [32], Sweden [33], Finland [34], and Mongolia [35]. In Central Europe [36], and in Italy [37], TBEV area was expanding to areas with higher elevation above sea level, which was also attributed to the warming climate. Recently, human cases of TBE were registered in Western Europe [38,39].…”
Section: Introductionmentioning
confidence: 84%
“…Tick-borne encephalitis virus (TBEV) is endemic throughout Central and Eastern Europe and has so far been detected in twenty-seven European countries. In the past decades, TBE human incidence has been increasing in several European countries ( ECDC, 2012 , 2018 ), with new foci detected in the United Kingdom ( Holding et al, 2020 ) and Netherlands ( Jahfari et al, 2017 ), expanding into previously unaffected areas ( Daniel et al, 2004 ; Lukan et al, 2010 ; Donoso Mantke et al, 2011 ; Martello et al, 2014 ; Brabec et al, 2017 ; Rieille et al, 2017 ; Hellenbrand et al, 2019 ; Alfano et al, 2020 ). These observations, associated with evidence of a recent increase in TBEV diversity in Europe, suggest that TBEV may be regarded as an emerging disease ( Deviatkin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%